The periodization of the history of regional anesthesia in medicine (Эндодонтия Today, 2020)
The article provides a historical periodization of development and introduction into medical practice regional anesthesia methods. We prove the priority role of Russian scientists in the scientifi c substantiation of the eff ectiveness of the method of regional anesthesia. Based on the studies suggested several periods of conductive anesthesia.